Clodoaldo Beckmann (1927–2007): o médico cirurgião e documentalista dedicado à Biblioteconomia - SOUZA, Orinete Costa (2015)
Study about the life and work of the surgeon and documentalist Clodoaldo Fernando Ribeiro Beckmann (1927-2007), founder of the Librarianship at the Universidade Federal do Pará (UFPA). It has the objective of recover the professional dimension of the man who has put his knowledge at service of the Medicine and Librarianship a study of qualitative nature was conducted, it was based on oral history, more precisely by biographic method, allied to documental and bibliographic research and the realization of open interviews and informal conversations with relatives, friends and ex-students. The memory recovered by evidences point the remarkable accomplishments of the Beckmann’s life that made his name entered into the history of Medicine and Librarianship in Pará.